Analysis On Students’ Difficulties of Finding Main Idea of A Passage - Puput Zuli Ekorini (STKIP PGRI Nganjuk, 2020)
This research was conducted to find students difficulties if getting main idea from a text and to know the students’ perspective of reading activity to find main idea. The subject of this research was the third semester students of English Department of STKIP PGRI Nganjuk which was consisted of 27 students. For getting the data, the researcher used three techniques they were reading test, interview, and providing questionnaire. As the results of the test there were 9 students who had score in range of 65-75 with the total questions of 20 and the rest had score in range of 40-64. Based on the interview, the students’ problems were about having low interest of reading, having low vocabulary mastery, the sentence structure which longer than what they usually read or construct, having poor reading strategy, and getting confused of grammatical structure used in the text. Based on the results of the questionnaire can be concluded that the third semester of English Department of STKIIP PGRI Nganjuk still had difficulties of getting main idea from a passage because mostly they did not understand with the vocabulary used in text so they could not determine the main idea of the passage.